The Awareness and Knowledge Levels of Building Information Modeling Among Architecture Students: A Survey-Based Study - Mehmet Ümit Meterelliyoz (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The present study aims to investigate the awareness of Building Information Modeling (BIM) in Turkey from students' perspectives. While numerous studies in the literature have explored BIM awareness in the industry, research specifically focused on students is scarce. Thus, this study aims to contribute a new and current perspective to the existing literature by measuring student awareness based on empirical evidence. By doing so, it intends to provide valuable insights for future research and curriculum development. The research utilized the results of a survey conducted in 2022 involving the participation of 34 fourth-year students in the architecture program. The findings indicate that students have heard about and even utilized the concept of Building Information Modeling, but their knowledge of this technological development needs to be more comprehensive. The survey was designed to assess the students' BIM awareness level to explore their understanding and proficiency in using BIM. The results revealed that students need to learn more about the technological elements and components that constitute BIM. This limitation hampers their potential to utilize BIM in practice effectively. The outcomes of this study underscore the necessity for architecture education programs to adopt a more comprehensive approach to BIM. Developing educational and informational strategies that enhance students' knowledge of BIM is imperative. The findings of this study serve as a valuable resource for increasing BIM awareness in architectural education and facilitating students' adaptation to this technology.